2008
DOI: 10.1007/s11103-008-9297-5
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast localization of methylerythritol 4-phosphate pathway enzymes and regulation of mitochondrial genes in ispD and ispE albino mutants in Arabidopsis

Abstract: Plant isoprenoids are derived from two independent pathways, the cytosolic mevalonate pathway and the plastid methylerythritol 4-phosphate (MEP) pathway. We used green fluorescent fusion protein assays to demonstrate that the Arabidopsis MEP pathway enzymes are localized to the chloroplast. We have also characterized three Arabidopsis albino mutants, ispD-1, ispD-2 and ispE-1, which have T-DNA insertions in the IspD and IspE genes of the MEP pathway. Levels of photosynthetic pigments are almost undetectable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
63
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 48 publications
(50 reference statements)
7
63
0
1
Order By: Relevance
“…Like the other albino mutants of the enzymes involved in MEP-related biosynthetic pathways, the dxr mutants exhibited an arrest in plastid development at early stages [20,22,30,[46][47][48]. This is consistent with the increased chlorophyll a/ b ratio observed in the pale inflorescence tissues, which are more sensitive to light due to the undeveloped plastids [49].…”
Section: Discussionsupporting
confidence: 63%
“…Like the other albino mutants of the enzymes involved in MEP-related biosynthetic pathways, the dxr mutants exhibited an arrest in plastid development at early stages [20,22,30,[46][47][48]. This is consistent with the increased chlorophyll a/ b ratio observed in the pale inflorescence tissues, which are more sensitive to light due to the undeveloped plastids [49].…”
Section: Discussionsupporting
confidence: 63%
“…However, it has been shown that the first 52 amino acids encompassing the predicted transit peptide of Arabidopsis HDR were sufficient to target the GFP reporter protein to the chloroplast. 14 In a recent report, we further demonstrated that the Arabidopsis HDRDNCD-GFP fusion protein was localized to the chloroplast. 21 Thus, the NCD is not required for targeting the Arabidopsis HDR enzyme to the chloroplast.…”
Section: -29mentioning
confidence: 70%
“…[14][15][16][17][18][19][20] The 4-hydroxy-3-methylbut-2-enyl diphosphate (HMBPP) reductase, commonly known as HDR, isoprenoid synthesis H (IspH), or lysis-tolerant B (LytB), catalyzes the last step of the MEP pathway that converts HMBPP into a 5:1 mixture of IPP and DMAPP in Escherichia coli. 12,13 In Arabidopsis thaliana, the hdr-1 knockout mutant is albino lethal and the HDR transgene-induced genesilencing lines are albino, pale green, or variegated.…”
mentioning
confidence: 99%
“…The chamomile sesquiterpenes are an adequate example showing clear metabolic crosstalk between the two pathways in which both provide IPP precursors for the production of certain terpenoids that consist of 2 five-carbon isoprene units, which are derivatives of the MEP pathway, while the third unit is formed by both pathways (Towler and Weathers 2007). In the plastids, the MEP pathway (Hsieh et al 2008) results in the formation of IPP and DMAPP from G3P and pyruvate. However, the classical independent MVA pathway (Vranová et al 2013) is disseminated in the cytosol, peroxisomes and endoplasmic reticulum (Pulido et al 2012).…”
Section: Biosynthesis and Subcellular Compartmentation Of Terpenoids mentioning
confidence: 99%